Exploring Vietnam; a quick getaway to Can Tho city - Ngoc - Phan Nguyen; Duong Dat; Tam - Truong Hoang (Bali Tourism Board, 2018)
Can Tho city is the central city of nine dragon river delta, Mekong river. International tourist may reach Can Tho city faster from Ho Chi Minh City International Airport. From the airport, the visitor may take a car or van. There are some unique places that worth to visit by the traveler. They are The Ong Pagoda and Ninh Kieu Quay. The Ong Pagoda is the oldest pagoda in Can Tho city while Ninh Kieu Quay, a port and cultural tourist destination of Can Tho city, was established in the 19th century. Settled in the delta of the Mekong river, makes the town becomes a place where traditional fuse in harmony with the growth of city hustle bustle. In the area, there are some beautiful landmarks with high historical value that worth to visit, as well as new gastronomy experiences in tasting Vietnamese-style cuisines.